Efektivitas Edukasi Video Tentang Personal Hygiene terhadap Pencegahan Penyakit Kulit ( Skabies) di Pondok Pesantren Rabiatul Adawiyah Baturaja: Effectiveness of Video Education About Personal Hygiene on Preventing Skin Disease (Scabies) at Rabiatul Adawiyah Islamic Boarding School Baturaja - Sulardi, Sulardi; Efrianty, Novalia; Fauziah, Nila Alfa; Anggesta, Meltia Dwi (Chakra Brahmanda Lentera Institute, 2025)
Skin diseases, including scabies, are common health problems in environments with poor hygiene, such as dormitories. Scabies is caused by the Sarcoptes scabiei mite and can be transmitted through direct contact or contaminated objects. Poor personal hygiene is a major factor in the spread of scabies, making it essential to increase knowledge about proper hygiene practices for prevention. Educational videos are an effective learning medium as they deliver information visually and interactively, enhancing understanding and hygiene practices. This study aims to analyze the effectiveness of educational videos on personal hygiene in preventing scabies at the Rabiatul Adawiyah Islamic Boarding School in Baturaja. The research design used a quasi-experiment with a pre-test and post-test design in one group. The research sample was 32 students selected using the total sampling method. Data were collected through questionnaires before and after the video education intervention. The results showed a significant increase in respondents’ knowledge after the educational video was given. The average pre-test score was 41.00 (low category), which increased to 80.13 (high category) in the post-test. The Paired T-Test analysis produced a p-value of 0.000 (p < 0.05), indicating a statistically significant difference between the knowledge levels before and after the intervention. However, the implementation of scabies prevention was not fully optimal, as most respondents were in the moderate category (81.3%), and only 18.8% reached the good category. Skin diseases, including scabies, are common health problems in environments with poor hygiene, such as dormitories. Scabies is caused by the Sarcoptes scabiei mite and can be transmitted through direct contact or contaminated objects. Poor personal hygiene is a major factor in the spread of scabies, making it essential to increase knowledge about proper hygiene practices for prevention. Educational videos are an effective learning medium as they deliver information visually and interactively, enhancing understanding and hygiene practices. This study aims to analyze the effectiveness of educational videos on personal hygiene in preventing scabies at the Rabiatul Adawiyah Islamic Boarding School in Baturaja. The research design used a quasi-experiment with a pre-test and post-test design in one group. The research sample was 32 students selected using the total sampling method. Data were collected through questionnaires before and after the video education intervention. The results showed a significant increase in respondents’ knowledge after the educational video was given. The average pre-test score was 41.00 (low category), which increased to 80.13 (high category) in the post-test. The Paired T-Test analysis produced a p-value of 0.000 (p < 0.05), indicating a statistically significant difference between the knowledge levels before and after the intervention. However, the implementation of scabies prevention was not fully optimal, as most respondents were in the moderate category (81.3%), and only 18.8% reached the good category.